Pengaruh Profesionalisme Dan Etika Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Pekerjaan Umum Dan Penataan Ruang Dan Pertanahaan (PUPRP) Kota Pariaman - Sri Mulyani; Rini Afrianti; Yanti Murni (CV. ITTC INDONESIA, 2025)
This research uses a quantitative approach. The population in this study were employees at the PUPRP service office with a sample size of 50 respondents. The data source in the research used primary data obtained from distributing questionnaires which were tested for validity and reliability. The data that has been obtained is then processed using the SPSS version 26 application. The data analysis technique in this research uses multiple linear regression, classical assumption testing, hypothesis testing and coefficient of determination. The research results showed that the multiple liner regression value Y = 7.159 + 0.309 X1 + 0.535 From the results of the coefficient of determination, the R² value is 0.743, meaning that the independent variable is able to influence the dependent variable by 74.3% while the remaining 25.7% is influenced by other variables not examined in this research.